2017
DOI: 10.1039/c7ra00452d
|View full text |Cite
|
Sign up to set email alerts
|

Microcapsules with a permeable hydrogel shell and an aqueous core continuously produced in a 3D microdevice by all-aqueous microfluidics

Abstract: We report the continuous production of microcapsules composed of an aqueous core and permeable hydrogel shell, made stable by the controlled photo-cross-linking of the shell of an all-aqueous double emulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…All‐aqueous emulsions, also called aqueous two‐phase system (ATPS), are immiscible aqueous phases generated by physical LLPS in aqueous polymer solutions . This emulsion system consists of droplets of one aqueous phase dispersed into the other aqueous phase.…”
Section: All‐aqueous Emulsions: Learning From Intracellular Llpsmentioning
confidence: 99%
See 1 more Smart Citation
“…All‐aqueous emulsions, also called aqueous two‐phase system (ATPS), are immiscible aqueous phases generated by physical LLPS in aqueous polymer solutions . This emulsion system consists of droplets of one aqueous phase dispersed into the other aqueous phase.…”
Section: All‐aqueous Emulsions: Learning From Intracellular Llpsmentioning
confidence: 99%
“…Inspired from the lipid bilayer of cell membrane, interfaces of all‐aqueous emulsions have been employed as 2D templates for fabrication of vesicles composed of a few macromolecular layers, including liposomes, polymersomes, and colloidosomes . Compared to the water–oil interface, the dynamic aqueous–aqueous interface has an ultralow interfacial tension, which gives rise to challenges and opportunities in macromolecular assembly at liquid–liquid interface .…”
Section: All‐aqueous Interface Templated Biomaterials: Assembly Of Armentioning
confidence: 99%
“…These results indicated that at low concentrations (5% (w/w)) of both DEX and PEG, it was difficult to generate droplets. However, when the concentrations of two solutions were increased to 10% (w/w), stable droplets were started to form even with lower molecule weight, compared to existing literature . Moreover, monodispersed droplets were easier to be generated when the concentrations of DEX and PEG were increased to more than 10% (w/w).…”
Section: Resultsmentioning
confidence: 69%
“…So far, two types of strategies are applied to obtain W/W droplets in microfluidic systems. One strategy is to use traditional flow focusing microfluidic device for droplets generation via a passive mode, but it cannot precisely control the size and morphology of W/W droplets. Another one is to generate droplets with external forcing on microfluidic chip, such as electrosprayed emulsion and periodic pulsating inlet pressures, but it is limited by the lower controllability and reproducibility resulting from the relative position variations of these external forces and microfluidic chip.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Biocompatible hydrogel microparticles have been previously produced using such methods as electrohydrodynamic jetting, [2] micromolding, [3] and microfluidics. [4] Among them, microfluidics is one of the most promising methods as it allows generation of multi-compartmentalized microparticles with precise control of dimensions and morphologies, [5] such as Janus-type, [6] coreshell, [7] and so-called "crescent-shaped" particles,that possess open cavities. [8] There have been attempts to use the crescentshaped microgels for confining enzymatic reactions for particle propulsion, [9] or for selective capture microscale objects,s uch as smaller particles or algae cells.…”
mentioning
confidence: 99%